Cluster structure and gateway availability of ad-hoc communication networks in the North Atlantic airspace - Marks, Tobias; Hillebrecht, Alexander (2022)
Data communication is an essential part of today's air traffic operations, enabling more flexible routing of aircraft and increased airspace capacity. While old generations of data link technology approach their technological limits, new technologies and approaches are being developed. Beside satellite communication and high frequency radio, one approach to enable data communication in remote, polar and oceanic airspaces such as the North Atlantic, is the establishment of aeronautical ad-hoc networks. Such networks are built up by direct data links between the aircraft which are acting as communication nodes, while ground connectivity is provided through dedicated gateway aircraft that are connected to ground. While the availability of gateways is strongly determined by the geographic location of the aircraft and ground stations, the connectivity of aeronautical ad-hoc networks is strongly influenced by the availability of gateways within clusters of inter-connected aircraft. In this paper, therefore, we follow an empirical approach to analyze the gateway availability and cluster structure on North Atlantic based on up to date flight plans. While an applicable set of ground stations is assumed that provides data transfer between ground and airborne network, we analyze the cluster structure and gateway availability by time-series analysis and present aggregated values for whole scenarios while varying the fraction of aircraft assumed to be equipped with the necessary technology as well as the air-to-air radio communication range. We show, that both factors have a strong influence on the formation of clusters and gateways and provide a starting point to derive requirements for the development of future communication technology.